PENGARUH LATIHAN PASSING BERPASANGAN TERHADAP KEMAMPUAN PASSING ATAS TIM BOLA VOLI PUTRA MADRASAH ALIYAH BAHRUL ULUM PANTAI RAJA - Syaifudin, Muhammad; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:The purpose of this research is to find out if there is the practice of passing in pairs on the ability of passing on the team volleyball men’s Madrasah Aliyah Bahrul Ulum Pantai Raja. So, when a (passing) get the capabilities of passing on a good. The research is research to the treatment of (Experimental), with a population team volleyball men’s Madrasah Aliyah Bahrul Ulum, the data in this research is the whole population of 12 people. The instruments used in this research is a test of passing the ball (passing), it aims to measure the ability of the passing up in volleyball. After that, the data is processed with statistics,to test normality with a lilifors test at significance level α (0.05). The hypothesis put forward is the influence of the exercise of passing in pairs on the ability of passing on. Based on the analysis of statistical data, the data pree test Lhitungof 0,1424, data post test Lhitungof 0,1369 and Ltabel 0,242, then Lhitung<Ltabel.then the data is normal with an increase of 6,08. Based on t test analysis produces Ttabel>Thitung of 6,4 and 1,796, meaning Thitung> Ttabel. Thus, there is the influence of exercise of passing in pairson the ability of passing on the team volleyball men’s Madrasah Aliyah Bahrul Ulum Pantai Raja.Keywords : passing in pairs, the ability of passing on.